Utilization Of Blockchain Technology In Human Resource Management - Joko Suhariyanto; Edi Sugiono; Andini Nurwulandari (Jurnal Ekonomi, 2024)
Blockchain, as a decentralized and secure technology, has the potential to address some of the key challenges faced by organizations in managing HR, such as transparency, data security, and process automation. This research aims to explore and analyze the potential use of blockchain technology in the context of human resource management (HR). This research uses a qualitative approach with descriptive methods The research results show that the use of Blockchain technology in human resource management (HR) has a significant positive impact. This technology successfully synchronizes and decentralizes financial records and employee personal data, increasing security, transparency and efficiency in various aspects of HR. Blockchain implementation reduces the risk of fraud, non-transparency and cyber threats in the recruitment process, credential verification, attendance management and financial management. The high security provided by Blockchain, supported by cryptography, makes transactions and payments safer, while the use of this technology provides a solid foundation for efficient and trusted HR management in the digital era. The results of this research highlight Blockchain's strategic role in shaping an innovative and sustainable future for the HR function.